S103 Using salivary pepsin and the reflux symptom index as objectives markers of gastro-oesophageal reflux to predict exacerbations of COPD. (12th November 2019) - Nootigattu, MS; Evans, RA; Steiner, MC; Greening, NJ
Abstract : Introduction: Self-reported gastro-oesophageal reflux disease (GORD) and associated laryngopharyngeal reflux (LPR) are common co-morbidities in patients with COPD and associated with an increased risk of exacerbations. 1 2 However, history of GORD or LPR are not routinely collected in these patients. Furthermore, silent reflux may predispose patients to exacerbations despite being asymptomatic. We aimed to determine the prevalence of objectively assessed measures of GORD and LPR, using salivary pepsin (a non-invasive biomarker of GORD, including silent disease) and the Reflux Symptom Index (RSI) respectively, and whether these were associated with exacerbations of COPD. Methods: Patients were recruited to a prospective cohort study from a complex COPD clinic in a tertiary centre. At baseline, patients completed the RSI questionnaire and provided saliva samples to be tested for salivary pepsin (Peptest). Patient demographics and exacerbation history in the previous three months were also collected. Results: 96 patients were recruited (mean [SD] age 66.5 [9.1] yrs., FEV1 %predicted 42.2 [18.6]%, CAT score 21 [8]). Self-reported GORD was present in 43 (45%) patients, abnormal RSI in 67 (70%) patients and positive salivary pepsin in 59 (62%) patients. A greater proportion of patients had at least one exacerbation in the previous three months if they had an abnormal RSI (84% vs 48%, p<0.001) but not if they were positive for salivary pepsin (75% vs 70%, p=0.644). Mean number of exacerbations was significantly greater in groups with self-reported GORD and an abnormal RSI (Figure 1). In a multivariate regression model, RSI was independently associated with an increased risk of having had an exacerbation in the last 3 months (OR: 5.01, p=0.004). No difference was seen with presence of salivary pepsin (OR:1.20, p=0.739) or self-reported GORD (OR: 2.39, p=0.147). Conclusions: Objectively measured GORD is common in patients with advanced COPD. Identification of LPR, using the RSI, is significantly associated with an increased risk of a previous exacerbation. Presence of salivary pepsin is not associated with increased risk of exacerbation. This observation needs to be validated for future exacerbation risk. References: Hurst, et al . NEJM 2010; 363:1128–1138 Jung, et al . Int J COPD 2015; 10: 1343–1351